Strong cosmological constraints on the neutrino magnetic moment - Carenza, Pierluca; Lucente, Giuseppe; Gerbino, Martina; Giannotti, Maurizio; Lattanzi, Massimiliano (Physical review, 2024)
A sizable magnetic moment for neutrinos would be evidence of exotic physics. In the early Universe, left-handed neutrinos with a magnetic moment would interact with electromagnetic fields in the primordial plasma, flipping their helicity and producing a population of right-handed (RH) neutrinos. In this work, we present a new calculation of the production rate of RH neutrinos in a multicomponent primordial plasma and quantify their contribution to the total energy density of relativistic species at early times, stressing the implications of the dependence on the initial time for production. We find that current cosmological data exclude values of the magnetic moment 𝜇 ≳1.6 ×10−11⁢𝜇𝐵, while future cosmological experiments will be able to probe nonthermal production of RH neutrinos, becoming competitive with stellar limits.